2002
DOI: 10.1080/1044667031000137584
|View full text |Cite
|
Sign up to set email alerts
|

Phage Display Based Cloning of Proteins Interacting with the Cytoplasmic Tail of Membrane Immunoglobulins

Abstract: The reduced quantity and quality of serum immunoglobulins (sIgs) in mutant mice expressing truncated cytoplasmic tails of IgE and IgG1 indicate an active role for the cytoplasmic domains of mIgG1 and mIgE. We used phage display technology to identify candidate proteins able to interact with the cytoplasmic tail of mIgE. Using a murine cDNA B cell library displayed on the surface of phage as prey and the 28 amino acid long cytoplasmic tail of IgE as bait, we isolated phage encoding the murine hematopoietic prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…We have shown that the adaptor protein, the HPK1-interacting protein of 55 kDa, is involved in the kinase activation of HPK1 by TCR stimulation (28). A recent phage display analysis found that HPK1 interacts with the cytoplasmic tail of membrane immunoglobulins (29). Although phosphorylation (4,5,7,(15)(16)(17)(18)30) and caspase-mediated cleavage (19,22) have been implicated in the regulation of HPK1, the details of the in vivo regulation of HPK1 remain largely unknown.…”
mentioning
confidence: 99%
“…We have shown that the adaptor protein, the HPK1-interacting protein of 55 kDa, is involved in the kinase activation of HPK1 by TCR stimulation (28). A recent phage display analysis found that HPK1 interacts with the cytoplasmic tail of membrane immunoglobulins (29). Although phosphorylation (4,5,7,(15)(16)(17)(18)30) and caspase-mediated cleavage (19,22) have been implicated in the regulation of HPK1, the details of the in vivo regulation of HPK1 remain largely unknown.…”
mentioning
confidence: 99%
“…Different regulation of BCR signaling through the B cell coreceptor CD22 was reported to be dependent on the distinct cytoplasmic tails ( and ␥) of the mIg isotypes (31). Also, for the -isotype, signal transduction was proposed to be different from other isotypes, including interactions of the cytoplasmic tail with specific cellular proteins (6,32). Moreover, it was recently reported that IgE ϩ cells could directly interact and trigger degranulation, in an Ag-independent manner, with mast cell and basophils expressing the FcRI (33).…”
Section: Discussionmentioning
confidence: 99%
“…HPK1 is activated by both EGF and PDGF stimulation where adaptor proteins are involved in mediating the localization of effector molecules to cell surface receptors [Anafi et al, 1997;Ling et al, 1999]. HPK1 also binds the cytoplasmic tail of IgE [Geisberger et al, 2002], but the functional significance of this interaction is unknown.…”
Section: Hpk1-mediated Cellular Signalingmentioning
confidence: 98%